2013
DOI: 10.3109/01480545.2013.776578
|View full text |Cite
|
Sign up to set email alerts
|

Study of oxidative, enzymatic mitochondrial respiratory chain function and apoptosis in perinatally HIV-infected pediatric patients

Abstract: Mitochondrial toxicity in perinatally human immunodeficiency virus (HIV)-infected pediatric patients has been scarcely investigated. Limited data are available about HIV or antiretroviral (ARV)-mediated mitochondrial damage in this population group, specifically, regarding oxygen consumption and apoptosis approach. We aimed to elucidate whether a given mitochondrial DNA depletion is reflected at downstream levels, to gain insight on the pathology of HIV and highly active antiretroviral therapy (HAART) in perin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…The global adverse perinatal outcome were significantly increased in HIV pregnancies, but did not correlate with mitochondrial or apoptotic findings. Several studies have demonstrated mitochondrial toxicity in animal models, HIV-infected infants and adults on NRTI therapy and newborns exposed in utero to ARVs [22,24,37,38,47], but it is currently unknown whether HIV-pregnancy may be an additional risk for the onset of mitochondrial toxicity.…”
Section: Mitochondrial and Apoptotic Parameters And Obstetrics Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The global adverse perinatal outcome were significantly increased in HIV pregnancies, but did not correlate with mitochondrial or apoptotic findings. Several studies have demonstrated mitochondrial toxicity in animal models, HIV-infected infants and adults on NRTI therapy and newborns exposed in utero to ARVs [22,24,37,38,47], but it is currently unknown whether HIV-pregnancy may be an additional risk for the onset of mitochondrial toxicity.…”
Section: Mitochondrial and Apoptotic Parameters And Obstetrics Resultsmentioning
confidence: 99%
“…Mitochondrial respiratory chain complex II+III (CII+III) enzymatic activities were measured by spectrophotometry according to Rustin et al [37,40] by following the increase in absorbance at 550 nm of reduced cytochrome c generation (complex III product) after succinate addition (complex II substrate). Specific enzymatic activities were expressed as nanomols of product per minute and milligram of protein (nmols/ min.mg prot).…”
Section: Mitochondrial Enzymatic Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…This PBMC model is widely feasible for the evaluation of mitochondrial function [21][22][23]. Thus, we designed the present study to evaluate mitochondrial dysfunction in both muscle and PBMCs of sIBM patients to correlate dysfunction severity with genetic and molecular mitochondrial alterations, and determine their potential association with the deregulation of mitochondrial dynamics.…”
Section: Introductionmentioning
confidence: 99%